KARAKTERISTIK PERSEPSI PENYAKIT DAN SKOR PHQ-9 PADA PASIEN PENYAKIT JANTUNG KORONER - Valerie Michaela Wilhelmina; Eva Suryani; Yunita Maslim (Bahasa Indonesia, 2021)
Introduction: Coronary Heart Disease (CHD) accounts for the largest proportion of cardiovascular diseases. CHD patients may experience depressive symptoms or major depressive disorder. Patient Health Questionnaire (PHQ-9) Score has good sensitivity and specificity for patients with CHD. Negative illness perception is significantly associated with more severe levels of depression. The aim of this study is to understand the characteristics of the perception of illness and PHQ-9 scores in patients with CHD at Atma Jaya Hospital, Jakarta. Methods: A cross-sectional research was done on CHD patients in the clinic of Internal Medicine and Cardiac Sub-Specialist clinics, Cosmas outpatient unit in Atma Jaya Hospital over the course of September-October 2015. The Brief Illness Perception Questionnaire (BIPQ) and PHQ-9 were used to assess the characteristics of illness perception and determine the level of depression in patients with CHD. Univariate analysis were used to process the data. Results: 42 patients met the inclusion criteria. 62% of subjects had a positive perception of the disease and 38% had a negative perception. The highest average score of B-IPQ was the illness concern. Majority of the subjects 48.8% had minimal depression and none of the subject had severe depression. Conclusion: B-IPQ scores indicated positive illness perception and PHQ-9 shows minimal depression in most of CHD patients